Managed Campaign and Bureaucratic Institutions in China: Evidence from the Targeted Poverty Alleviation Program. Issue 123 (3rd May 2020) - Zeng, Qingjie
ABSTRACT: In the reform era, the Chinese state often resorts to managed campaigns to implement important policies. This article examines how managed campaign influences the mode of bureaucratic operation in China. Avoiding a simplistic dichotomy between campaign mobilization and bureaucratic institutionalization, this study unpacks the Weberian bureaucratic concept and shows that some core dimensions of the model are compatible with managed campaign. While the pressure of mobilization tend to compromise functional differentiation and strict adherence to stable rules, they can reinforce other dimensions such as top-down control in a multilevel hierarchy and procedural integrity. The Chinese Communist Party (CCP) has configured the bureaucracy to serve its organizational and political needs, resulting in a mode of operation that partially conforms to the Western standard of public administration.